2012
DOI: 10.1097/bpb.0b013e328354b08c
|View full text |Cite
|
Sign up to set email alerts
|

Acute traumatic posterior elbow dislocation in children

Abstract: Traumatic posterior dislocation of the elbow is often associated with significant morbidity and incomplete recovery. The aim of this study was to retrospectively analyse the outcome of 33 children (median age 10.8 years). Patients underwent reduction and assessment of stability under general anaesthesia. Pure dislocations (n=10) were immobilized, whereas unstable fractures (n=23) were stabilized. Refixation of ligaments was performed if stability was not achieved by fracture stabilization alone. Immobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 31 publications
1
52
0
6
Order By: Relevance
“…The youngest reported patient with pure elbow dislocation in the literature was an 18 month-old child [4]. Limited numbers of studies discussing pure elbow dislocation in the paediatric age group have been published in the literature [1,3,7,8,10,16]. Di Gennaro et al [20] reported that dislocation of the elbow in children was a benign injury in the majority of cases and had a good prognosis.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The youngest reported patient with pure elbow dislocation in the literature was an 18 month-old child [4]. Limited numbers of studies discussing pure elbow dislocation in the paediatric age group have been published in the literature [1,3,7,8,10,16]. Di Gennaro et al [20] reported that dislocation of the elbow in children was a benign injury in the majority of cases and had a good prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…Posterior elbow dislocations comprise over 90 % of the cases [2,3,10]. Unusual types of dislocations, such as the terrible triad, divergent or convergent dislocations or with crossover of the radius and ulna, were also reported in the literature [13,17,21,22].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations